Aesthetics and style in strategy - Ferriani, Simone; Godart, édéric; V Sgourev, Stoyan; Cattani, Gino (Advances in strategic management, 2020)
This book contains an Open Access chapter Scholarship in management and strategy is paying increasing attention to the domain of aesthetics. Companies routinely make aesthetic choices and there is growing recognition that aesthetic considerations are fundamental for successful performance in competitive markets. Stylistically sophisticated products may appeal to demanding customers, yielding higher profit margins. Style and beauty can also be applied toward enriching organizational cultures, informing leadership visions or motivating employees to defy conventions in designing new products. Aesthetics and Style in Strategy constitutes the first systematic survey of the interface between the aesthetic and strategic domains. Motivated by the rise of aestheticism in contemporary culture, it lays the foundations for an "aesthetic" turn in strategy, which interrogates the use of aesthetic features as a source of competitive advantage and provides examples of connecting design and engineering, style and technology. The "aesthetic turn" is not simply about creating value, but about sharing value among employees and infusing organizational activities with a purpose that transcends principles of efficiency. Volume 42 of Advances in Strategic Management documents the variety of ways in which the useful and the beautiful can be brought together, making a valuable contribution to the sustainability of business in the 21st century.